Primary Congenital Glaucoma: Detecting Novel Disease-Causing Variants Using Whole-Exome Sequencing and Pathway Analysis - Ghaffarian Zavarzadeh, Parisima; Shalbafan, Bita; Abdi, Fatemeh (Journal of Ophthalmic and Optometric Sciences, 2020)
Abstract Primary Congenital Glaucoma (PCG) is an irreversible loss of vision that occurs mainly in infants or in the first years of life. In addition to numerous sporadic cases, PCG exhibits both an autosomal recessive and an autosomal dominant mode of inheritance. The genetic etiology of the disease is not fully understood; however, the role of genes such as CYP1B1, MYOC, LTBP2, and TEK is recognized. Various molecular biology approaches have been developed to study various diseases’ genetic and signaling patterns, especially PCG. Due to the genetic etiology is essential to consider genetic counseling for patients and their families who tend to be at higher risk and eventually reduce the prevalence of ocular diseases. In this review, in addition to examining various aspects of the disease, we specifically focused on the Molecular and Genetic Basis of PCG, including a small aspect of whole-Exome Sequencing to detect novel disease-causing variants. Keywords: Cytochrome P-450 CYP1B1; Glaucoma; Genetic Counseling; Whole-Exome Sequencing.